Makna Tuturan Budaya Hase Hawaka pada Masyarakat Desa Nanaet Kecamatan Nanaet Duabesi Kabupaten Belu-NTT - Theresia Kolo; Adrianus Berek; Oktaviana M.F.Q. Bobe (Jurnal Pendidikan Dirgantara, 2025)
This study aims to describe and analyze the meanings contained in the cultural utterance Hase Hawaka among the people of Nanaet Village, Nanaet Duabesi District, Belu Regency, East Nusa Tenggara. Hase Hawaka is a traditional expression that has been passed down from generation to generation, embodying deep social, moral, and spiritual values within the community. The study employs a qualitative approach using structural theory to reveal the implicit meanings embedded in this traditional discourse. Data were collected through observation and interview methods, supported by note-taking and recording techniques to obtain authentic data from native speakers. The results show that Hase Hawaka serves not only as a means of traditional communication but also as a medium for cultural education that conveys values of respect, unity, and social responsibility. Furthermore, the meanings contained within Hase Hawaka reflect the community’s worldview about the balance between humans, nature, and the Creator. Therefore, Hase Hawaka plays an important role in preserving cultural identity and strengthening the social cohesion of the Nanaet community.